The Influence of Internal Factors and Sustainable Investment Banking on ESG-Based Banking Profitability - Putri, Irmadanti Ananda; Susilo (Contemporary Studies in Economic, Finance and Banking, 2026)
This study aims to determine and analyze the influence of operational efficiency, management quality, liabilities, and Sustainable Investment Banking on the profitability of banks implementing Environmental, Social, and Governance (ESG) principles in Indonesia. The application of sustainability principles in the banking sector is increasingly important with increasing attention to responsible financial activities. This study uses a quantitative approach with secondary data obtained from the annual reports and sustainability reports of four major banks listed on the Indonesia Stock Exchange: Bank Mandiri, Bank Rakyat Indonesia, Bank Central Asia, and Bank Negara Indonesia for the period 2010–2024. The analytical method used is panel panel unbalanced data regression to examine the relationship between the research variables. The results show that operational efficiency, management quality, liabilities, and Sustainable Investment Banking have a significant influence on bank profitability. These findings suggest that efficient operational management and the implementation of sustainable investment activities can support improved banking performance in the long term.